Taking appreciation to heart: appreciation at work and cardiovascular risk in male employees - Auer, Alisa; Semmer, Norbert K.; von Känel, Roland; Thomas, Livia; Zuccarella-Hackl, Claudia; Wiest, Roland; Wirtz, Petra H. (Frontiers in Public Health, 2024)
Introduction While perceived appreciation at work has been associated with self-reported health and wellbeing, studies considering biological health markers are lacking. In this study, we investigated whether appreciation at work would relate to coronary heart disease (CHD) risk as well as the specificity of this proposed association. Methods Our study comprised a total of 103 male participants, including apparently healthy, medication-free, non-smoking men in the normotensive to hypertensive range (n = 70) as well as medicated hypertensive and CHD patients (n = 33). CHD risk was assessed by blood pressure [mean arterial pressure (MAP)], the diabetes marker glycated hemoglobin A1c (HbA1c), blood lipids [total cholesterol (TC)/high-density lipoprotein-cholesterol (HDL-C) ratio], coagulation activity (D-dimer and fibrinogen), and inflammation [interleukin (IL)-6, tumor necrosis factor-alpha (TNF-α), and C-reactive protein (CRP)]. Perceived appreciation at work, as well as potentially confounding psychological factors (social support, self-esteem, and work strain due to a lack of appreciation), were measured by self-report questionnaires. Results We found higher appreciation at work to relate to lower overall composite CHD risk (p’s ≤ 0.011) and, in particular, to lower MAP (p’s ≤ 0.007) and lower blood lipids (p’s ≤ 0.031) in medication-free participants as well as all participants. This overall association was independent of confounding factors, including related psychological factors (p’s ≤ 0.049). Discussion Our findings indicate that appreciation at work might be an independent health-promoting resource in terms of CHD risk. Implications include that encouraging appreciation at work may help reduce the development and progression of CHD.